2003
DOI: 10.1021/es021005u
|View full text |Cite
|
Sign up to set email alerts
|

Particle Growth by Acid-Catalyzed Heterogeneous Reactions of Organic Carbonyls on Preexisting Aerosols

Abstract: Aerosol growth by the heterogeneous reactions of different aliphatic and alpha,beta-unsaturated carbonyls in the presence/absence of acidified seed aerosols was studied in a 2 m long flow reactor (2.5 cm i.d.) and a 0.5-m3 Teflon film bag under darkness. For the flow reactor experiments, 2,4-hexadienal, 5-methyl-3-hexen-2-one, 2-cyclohexenone, 3-methyl-2-cyclopentenone, 3-methyl-2-cyclohexenone, and octanal were studied. The carbonyls were selected based on their reactivity for acid-catalyzed reactions, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
143
3
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(150 citation statements)
references
References 38 publications
2
143
3
2
Order By: Relevance
“…It may also be possible that these small oxygenated compounds are present in the particle phase not only as parent compounds, but also as thermal decomposition products of unstable peroxides (24) and/or the decomposition product of larger oligomers (25)(26)(27). Ultimately, there are several explanations that would point toward additional SOA compared to theoretical SOA production.…”
Section: Phase Transitioning By Compound Class and Molecular Sizementioning
confidence: 99%
“…It may also be possible that these small oxygenated compounds are present in the particle phase not only as parent compounds, but also as thermal decomposition products of unstable peroxides (24) and/or the decomposition product of larger oligomers (25)(26)(27). Ultimately, there are several explanations that would point toward additional SOA compared to theoretical SOA production.…”
Section: Phase Transitioning By Compound Class and Molecular Sizementioning
confidence: 99%
“…However, it has also been shown that other factors influence the SOA yield, i.e. the mass of organic aerosol that can serve as solvent for semivolatile organic compounds (Pankow, 1994;Odum et al, 1996), the acidity of and chemical reactions in the particulate phase (Jang et al, 2003;Gao et al, 2004;Iinuma et al, 2004;Kalberer et al, 2004), the humidity (Bonn et al, 2002;Jonsson et al, 2006), and the temperature that controls the phase equilibrium of the semivolatile organics and also influences the reaction pathways leading to condensable molecules (Sheehan and Bowman, 2001;Takekawa et al, 2003;Jenkin, 2004;Offenberg et al, 2006;Pathak et al, 2007b;Stanier et al, 2007;Johnson and Marston, 2008). There has been a considerable amount of work on aerosol yields from the ozonolysis of α-pinene or limonene near room temperature (290-303 K) e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A significant fraction of the organic aerosol material remains uncharacterised, and the thermodynamic properties of the secondary compounds that have been identified (e.g., Yu et al, 1999;Jaoui et al, 2005) have generally not been measured. Evidence suggests that oligomerisation and other aerosol phase reactions can be important, and enhance the formation of secondary organic aerosol (SOA) material (Jang et al, 2003;Kalberer et al, 2006). The most common atmospheric codes treat the organic components of aerosols, including SOA formation, using a lumped two component approach developed to represent the results of chamber experiments (Odum et al, 1996;Griffin et al, 1999).…”
mentioning
confidence: 99%